Opens typology architecture of Islam (Case study : Bayt Al Qur’an and Museum Istiqlal) - Wahid, Julaihi; Alamsyah, Bhakti (2008)

(untitled)
Progress of technology that is increasingly fast more enablingly man to innovate in finding a new findings, do not aside from in architecture area. From civilization of man who nomad, formerly lived in tree house, caves until finally permanent and makes shacks and then rounds into traditional houses which there are still up to now. Requirement would a protection of nature for all man activities increasingly grows along with development of man activity, causing emerges a new notchings in designing building. Besides house, building that is in general as place of man activity also experiences development that is enough significant. But appearance of building having new notchings itself always generates pro and counter where, especially in state which tropical climate. Borns it the new notchings always also followed by bases and methods realized also in conceptioning has just in architecture which can accompany bearing it a form of new building. Bolts from the thing, Ir. Achmad Noe'man, which is an architect in Indonesia trying to make a new breakthrough in designing building and always bears a new concept in finding new notchings which in basing to understanding of architecture having nuance Islamic. Bayt Al Qur'an and Museum Istiqlal is some of masterpiece Ir. Achmad Noe'man will be applied as case which will represent in business to find has present a new type in developing architecture concept is having nuance Islamic as well as as an impregnation of form or building types in architecture in general.